Hyaluronan Produced by Smooth Muscle Cells Plays a Critical Role in Neointima Formation. (12th May 2014) - Vigetti, Davide; Deleonibus, Sara; Karousou, Eugenia; Viola, Manuela; De Luca, Giancarlo; Passi, Alberto
Abstract : Large body of evidence supports the idea that microenvironment plays a critical role in several pathologies including atherosclerosis and cancer. The amount of hyaluronan (HA) is involved in the microenvironment alterations and the concentration of this polymer reflects the progression of the diseases promoting neoangiogenesis, cell migration, and inflammation. The HA synthesis is regulated by several factors: UDP sugar precursors availability and the phosphorylation of synthetic enzyme HAS2 as well as specific drugs reducing the UDP precursors. The HAS2 phosphorylation is done by AMP kinase, a sensor of cell energy. When the cells have low energy, AMP kinase is activated and modifies covalently the regulatory enzymes, blocking all biosynthetic processes and activating the energy producing metabolism. It was recently reported that the hexosamine biosynthetic pathway (HBP) may increase the concentration of HA precursor UDP-N-acetylglucosamine (UDP-GlcNAc) leading to an increase of HA synthesis. We demonstrated that the increase of HA synthesis depends on the HAS2 post translational modification O-GlcNAcylation, which increases HA secretion modifying a residue different from the phosphorylation site of AMP kinase. In this report we highlighted the critical aspects of the post translational HAS2 regulation and its influence on HA synthesis.